ANALISIS KERAGAAN AGROINDUSTRI TAHU KULIT DI KELURAHAN GUNUNG SULAH KECAMATAN WAY HALIM KOTA BANDAR LAMPUNG - Shafira, Fadila; Lestari, Dyah Aring Hepiana; Affandi, Muhammad Irfan (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This research aims to analyze the raw material procurement system based on the elements of raw materials, the performance of production, income and added value associated with the processing activities, marketing mix and distribution channel in product marketing activities, and the role of support services. The research method used was a case study method on three â€œtahu kulitâ€ agro-industries in Gunung Sulah Urban Village, Way Halim Sub-district, Bandar Lampung City. The location of research was determined purposively with the consideration that the Gunung Sulah Urban Village was the center of â€œtahu kulitâ€ production in Bandar Lampung.Â  Research was conducted in February - March 2017 and data analysis method used in this research was qualitative and quantitative descriptive analysis.Â  The results showed that the procurement of raw materials in the three agro-industries was in accordance with the elements of procurement of raw materials.Â  The production performance of the three agro-industries had not been good because it had not fulfilled the productivity and flexibility components. Revenues of the three agro-industries were good because the values of R / C ratio were more than 1 and processing of these three agro-industries adds positive value. Â Three agro-industries had implemented a marketing mix and there are two channels in marketing activities of â€œtahu kulitâ€ product. Support services utilized by agro-industries gave positive impact to agro-industry activities.Key words: added value, agroindustry, income, performance, tahu kulit